Institutional investors' power to change corporate behaviour international perspectives - Young, Suzanne; Gates, Stephen (Critical studies on corporate responsibility, governance and sustainability ;, 2013)
The aim of the book series is to explore public concerns and practical issues deeply and rethink theoretical debates and institutional policies critically in the broad area of corporate responsibility, corporate governance and sustainability around the world. It examines the social, economic and environmental impacts of corporations, and the real effects of corporate governance, CSR and business sustainability on societies in different regions. It facilitates a better understanding of how value systems, cultures and traditions in different societies may affect the policies and practices of corporate responsibility, governance and sustainability. It identifies the future development trends of corporate responsibility, governance and sustainability in contexts when examining and exploring those key issues.